Technology of formation of psychological climate in team sports games (on the material of volleyball) - Doroshenko, E. Yu.; Oliinyk, I.; Melnyk, M.; Oliinyk, M. O.; Sheviakov, O.; Дорошенко, Едуард Юрійович; Олійник, Михайло Олександрович (My University, 2022)
Purpose of the work – scientifically substantiate the technology of forming the optimal psychological climate in volleyball to increase the effectiveness of competitive activities of athletes. Material and methods. The experimental studies involved 25 qualified volleyball players - 13 athletes of VC “Orbita‑ZNU-RCYSS” (Zaporizhzhya), main group, and 12 athletes of VC “Polissya-SНSM-ZhDU (Zhytomyr), control group. Analysis and generalization of scientific and methodological literature and the Internet; method “Diagnosis of personality for motivation to succeed” (by T. Ehlers); method “Assessment of moral and psychological climate in the team” (according to L. Lutoshkin); method “Assessment of the psychological atmosphere in the team” (according to L. Zhedunova). Analysis and evaluation of competitive performance indicators. Pedagogical experiment. Statistical analysis. Results. The developed technology of optimization of psychological climate in volleyball contains the corresponding terms of application in a macrocycle of preparation: four consecutive developing complexes of psychological means (exercises, games and trainings). The technology of optimization of the psychological climate in the sports team of qualified volleyball players included specially developed psychological and pedagogical tasks, exercises, situational role-playing games. Interpretation and generalization of experimental research indicators allows us to state that the athletes of VC “Orbita-ZNU-RCYSS” (Zaporizhzhya) in 80% of cases have a tendency to correlate the indicators of optimizing the psychological climate and increase the effectiveness of competitive activities. Conclusions. The developed technology of optimization of psychological climate in volleyball contains the corresponding terms of application in a macrocycle of preparation: four consecutive developing complexes of psychological means (exercises, games and trainings). The technology of optimization of the psychological climate in the sports team of qualified volleyball players included specially developed psychological and pedagogical tasks, exercises, situational role-playing games. Interpretation and generalization of experimental research indicators allows us to state that the athletes of VC “Orbita-ZNU-RCYSS” (Zaporizhzhya) in 80% of cases have a tendency to correlate the indicators of optimizing the psychological climate and increase the effectiveness of competitive activities. підвищення ефективності змагальної діяльності спортсменок.. Матеріали і методи. В експериментальних дослідженнях брали участь 25 кваліфікованих волейболісток – 13 спортсменок ВК «Орбіта-ЗНУ-ОДЮСШ» (Запоріжжя), основна група, та 12 спортсменок ВК «Полісся-ШВСМ-ЖДУ» (Житомир), контрольна група. Аналіз та узагальнення науково-методичної літератури і мережі «Internet»; методика «Діагностика особистості на мотивацію до успіху» (за Т. Ehlers); методика «Оцінка морально-психологічного клімату у колективі» (за Л. Лутошкіним); методика «Оцінка психологічної атмосфери у колективі» (за Л. Жедуновою). Аналіз та оцінка показників ефективності змагальної діяльності. Педагогічний експеримент. Статистичний аналіз. Результати. Після впровадження розробленої технології оптимізації психологічного клімату у тренувальний процес ВК «Орбіта-ЗНУ-ОДЮСШ» (Запоріжжя), констатуємо наявність тенденції до знижених показників взаємозв’язку мотивації до успіху особистості та атакувальних техніко-тактичних дій у змагальній діяльності волейболісток за тестами Т. Елерс «Діагностика особистості на мотивацію до успіху», Л. Лутошкін «Оцінка морально-психологічного клімату у колективі» та Л. Жедунова «Оцінка психологічної атмосфери у колективі»: r = 0,124, r = 0,496 і r = 0,477 відповідно. За іншими показниками техніко-тактичних дій (набрані очки, подача м’яча, блокування, прийом м’яча) зафіксовано високі значення показників коефіцієнту кореляції. Висновки. Розроблена технологія оптимізації психологічного клімату у волейболі містить відповідні терміни застосування у макроциклі підготовки: чотири послідовних розвивальних комплекси психологічних засобів (вправ, ігор і тренінгів). До складу технології оптимізації психологічного клімату в спортивній команді кваліфікованих волейболісток увійшли спеціально розроблені психолого-педагогічні завдання, вправи, ситуаційно-рольові ігри. Інтерпретація та узагальнення показників експериментальних досліджень, дозволяє констатувати, що у спортсменок ВК «Орбіта-ЗНУ-ОДЮСШ» (Запоріжжя) у 80% випадків, наявна тенденція до взаємозв’язку показників оптимізації психологічного клімату та підвищення ефективності змагальної діяльності.
Технологія формування психологічного клімату у командних спортивних іграх (на матеріалі волейболу)
Doroshenko E. Yu. - https://orcid.org/0000-0001-7624-531X; Oliinyk M. O. - https://orcid.org/0000-0003-4131-7664.
Keywords: volleyball; formation; technology; optimization; psychological climate; волейбол; формування; технологія; оптимізація; психологічний клімат